Chronic Lymphocytic Choriomeningitis Infection Causes Susceptibility to Mousepox and Impairs Natural Killer Cell Maturation and Function - Alves-Peixoto, Pedro (J Virol, 2020)
Chronic viral infections. like those of humans with cytomegalovirus, human immunodeficiency virus (even when under antiretroviral therapy), and hepatitis C virus or those of mice with lymphocytic choriomeningitis virus (LCMV) clone 13 (CL13), result in immune dysfunction that predisposes the host to severe infections with unrelated pathogens. It is known that C57BL/6 (B6) mice are resistant to mousepox, a lethal disease caused by the orthopoxvirus ectromelia virus (ECTV), and that this resistance requires natural killer (NK) cells and other immune cells. We show that most B6 mice chronically infected with CL13 succumb to mousepox but that most of those that recovered from acute infection with the LCMV Armstrong (Arm) strain survive. We also show that B6 mice chronically infected with CL13 and those that recovered from Arm infection have a reduced frequency and a reduced number of NK cells. However, at steady state, NK cells in mice that have recovered from Arm infection mature normally and, in response to ECTV, get activated, become more mature, proliferate, and increase their cytotoxicity in vivo. Conversely, in mice chronically infected with CL13, NK cells are immature and residually activated, and following ECTV infection, they do not mature, proliferate, or increase their cytotoxicity. Given the well-established importance of NK cells in resistance to mousepox, these data suggest that the NK cell dysfunction caused by CL13 persistence may contribute to the susceptibility of CL13-infected mice to mousepox. Whether chronic infections similarly affect NK cells in humans should be explored. IMPORTANCE Infection of adult mice with the clone 13 (CL13) strain of lymphocytic choriomeningitis virus (LCMV) is extensively used as a model of chronic infection. In this paper, we show that mice chronically infected with CL13 succumb to challenge with ectromelia virus (ECTV; the agent of mousepox) and that natural killer (NK) cells in CL13-infected mice are reduced in numbers and have an immature and partially activated phenotype but do respond to ECTV. These data may provide additional clues why humans chronically infected with certain pathogens are less resistant to viral diseases.